Assessment of Heavy Metals in Water, Sediment, and Fishes of a Large Tropical Hydroelectric Dam in Sarawak, Malaysia - Siong Fong Sim; Teck Yee Ling; Lee Nyanti; Norliza Gerunsin; Yiew Ee Wong; Liang Ping Kho (Journal of Chemistry)
Bakun Hydroelectric Dam in Sarawak is one of the world highest concrete rock filled dams. This paper reports the heavy metals concentrations in water, sediment, and fishes of Bakun Dam. Water and sediment samples were collected from 11 stations and 6 fish species were caught. The samples were digested with open acid digestion and the metals contents were analysed using an atomic absorption spectrophotometer and mercury analyser. The method was validated based on certified reference materials. A higher concentration of Fe and Mn was detected in downstream water with significant longitudinal variation. Cu, Zn, and Hg were present in trace amount. All elements analysed were consistently found in sediment with no risk of contamination. For fish, Hemibagrus planiceps was characterised by higher affinity for Hg accumulation. The concentrations detected in all fish species were within the permissible guideline of 0.5 mg/kg. The health risk assessment suggested that Barbonymus schwanenfeldii, Puntioplites waandersii, Cyclocheilichthys apogon, and Hemibagrus planiceps were characterised by hazard index > 1 implying possible adverse effects. The amount of fish recommended for adults and children was in the range of 500–775 g/week and 33–135 g/week, respectively.